Biodegradation ability and physiological responses of cyanobacterium Leptolyngbya sp. ISC 25 under naphthalene treatment - Panah, B.A.; Najafi, F.; Soltani, N.; Nejad, R.A.Kh.; Babaei, S. (Альгология, 2015)
Cyanobacteria (Cyanoprokaryota) have gained a lot of attention in recent years because of their potential applications in biotechnology. In this study the cyanobacterium Leptolyngbya sp. ISC 25 was identified as tolerating and effectively degrading naphthalene as a toxic compound in the environment. Исследование посвящено изучению физиологических реакций цианобактерии Leptolyngbya sp. ISC 25 при воздействии нафталина. Показано, что данный штамм устойчив к нафталину и способен эффективно разлагать его токсичные соединения в окружающей среде.